2003
DOI: 10.1016/s0886-3350(03)00332-8
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic subconjunctival crystalline lens dislocation

Abstract: With timely intervention, the visual outcome was reasonably good in patients with subconjunctival dislocation of the crystalline lens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 8 publications
3
13
0
3
Order By: Relevance
“…A similar finding was also reported by Yurdakul et al 5 However, Charan and Mathur6 reported inferior displacement and Krámar et al 7 reported superotemporal displacement of lens following blunt trauma. Subconjunctival luxation of crystalline lens is very rare in children due to elasticity of outer coats of the globe and softer crystalline lens.…”
Section: Discussionsupporting
confidence: 81%
“…A similar finding was also reported by Yurdakul et al 5 However, Charan and Mathur6 reported inferior displacement and Krámar et al 7 reported superotemporal displacement of lens following blunt trauma. Subconjunctival luxation of crystalline lens is very rare in children due to elasticity of outer coats of the globe and softer crystalline lens.…”
Section: Discussionsupporting
confidence: 81%
“…[3] Another report highlights the role of UBM in the precise localization of phacocele and its utility on the surgical planning. [4] A review of literature for phacocele shows isolated case reports and only two case series of five[5] and eight cases[6] each. Both of these series highlight the clinical features and outcome.…”
Section: Discussionmentioning
confidence: 99%
“…El estallido ocular suele producirse en el sector nasal superior por la proyección de la energía del impacto desde temporal, sector en el que suelen producirse los impactos con más frecuencia (5). La energía se proyecta hacia superior, posterior y nasal, impactando el globo contra la tróclea y la pared orbitaria (2)(3)(4)(5).…”
Section: Discussionunclassified
“…La energía se proyecta hacia superior, posterior y nasal, impactando el globo contra la tróclea y la pared orbitaria (2)(3)(4)(5). Normalmente la ruptura se produce a 2,5 mm y concéntrica al limbo, donde las fibras esclerales tensas y profundas se transforman en una lamela delicada de ligamento pectíneo (3).…”
Section: Discussionunclassified